Design Of Mems Inductor And Varactor For Low Noise Voltage Controlled Oscillators - Rahimi, Maryam (2009)
Micro-Electro-Mechanical-Systems (MEMS) technology has been used to develop high quality factor (Q), low cost and low power consumption circuit blocks in RF communication systems. This research focuses on the design of high-performance MEMS inductor and varactor for use in Complementary Metal-Oxide Semiconductor (CMOS) voltage controlled oscillators (VCO) operating at 2.4 GHz. The air suspended inductor has been designed using MEMS technology to reduce the resistive loss and the substrate loss. Lowresistivity material has been used. A MEMS two-gap tunable capacitor, using two parallel plates (one fixed and one movable), has been designed. The capacitance can be varied by applying low voltage to the movable plate. The pull-in voltage has been optimized to achieve low phase noise, low power consumption, and a wide frequency tuning range for VCO. The MEMS inductor and MEMS capacitor have been used in the design of VCO. The inductor has been modeled with a physical, equivalent two-port model known as Yue's model to compute the parameters and Q factor of the inductor. The designed inductor has a Q factor of 27 and the inductance is about 2.87nH at 2.4GHz. The capacitor has a value of 2.04 pF capacitance and Q factor of 40 at 2.4 GHz. The proposed MEMS inductor and varactor has been used in simulation of VCO to determine the effect of high Q factor on the VCO phase noise. The active part of the circuit has been designed using CMOS. Based on the simulation, low phase noise and low power consumption have been obtained simultaneously. The results of - 117.7 dBc/Hz at 1 00 KHz and 11m W have been achieved for phase noise and power consumption of VCO respectively.